Relationship between maternal autonomy support, playfulness, and emotion regulation among pre-schoolers in Klang Valley, Malaysia - Sii, Hung Ee; Arshat, Zarinah; Ismail, Nellie (Human Resource Management Academic Research Society, 2023)
The aim of this study is to determine the relationships between maternal autonomy support (autonomy-supportive and controlling parenting), playfulness, and emotion regulation among pre-schoolers in Klang Valley. A total of 103 mothers with pre-schoolers aged between four and six years old were recruited with a multistage cluster sampling technique. The instruments used in this study were Perceived Parental Autonomy Support (P-PASS) to measure maternal autonomy support, Children’s Playfulness Scale (CPS) to measure playfulness, and Emotion Regulation Checklist (ERC) to measure emotion regulation. The findings revealed a significant positive relationship between autonomy-supportive parenting and emotion regulation and a significant negative relationship between controlling parenting and emotion regulation. However, the relationship between a child’s playfulness and a child’s emotion regulation was not significant. Multiple regression analysis was used to identify the independent variables that could predict emotion regulation. The findings indicated controlling parenting and autonomy-supportive parenting to be significant predictors of emotion regulation among pre-schoolers. The study concluded that autonomy-supportive parenting and controlling parenting had different significant associations with a child’s emotion regulation. Hence, the finding could provide valuable information to parents and educators to provide autonomy support to develop emotion regulation among pre-schoolers.